The Development of A Web Blog for Learning English Grammar - Dewi Furwana; Andi Tenrisanna Syam; Qubra Qubra (Universitas Syiah Kuala, 2023)
This research aimed to develop the appropriate weblog for learning English grammar of the twelfth-grade students at SMAN 4 Palopo. Furthermore, the researcher applied Research and Development (RD) method under the ADDIE model by Reiser and Mollanda in 1967. It comprises five phases: Analysis, Design, Development, Implementation, and Evaluation. This research was located at SMAN 4 Palopo. The subjects in the research were the twelfth-grade students at SMAN 4 Palopo, and 42 students became respondents for the development tryout. This research used several instruments to collect data, i.e., need analysis questionnaires, experts’ judgment questionnaires, and students’ perception questionnaires. The technique of data analysis was a quantitative descriptive analysis technique. This research shows that the developed basic English grammar material through blog learning for the twelfth-grade students at SMAN 4 Palopo was appropriate. The value from the expert’s validation showed that the material expert was 4.33, the language expert was 4.80, and the media/IT expert was 3.44. Thus, the overall mean score for product validity was 4.52 under the excellent category. The result of the questionnaire on students’ perception obtained 4.23 in the excellent category.